Illness and femininity in Hilary Mantel's Giving Up the Ghost (2003). Issue 6 (3rd July 2019) - Vickers, Neil
ABSTRACT: This paper offers a reading of Hilary Mantel's memoir, Giving Up The Ghost (2003). The interest of the memoir derives from the fact that it provides an exceptionally rich picture of the impact of family life on a child's attitudes towards her own body. Mantel presents her bodily experiences as primitive, often unconscious, perceptions of the relationships within her family of origin. When she discovers new things about those relationships, she must register the change through her body in some way. Drawing on a range of concepts taken from psychoanalytic psychosomatics, I suggest that at the heart of the memoir is the author's bafflement at the repeated and uncanny irruption of a conflict between her body as a somewhat autonomous signifying entity and the psychological strength she seeks and often finds through identifications with family members. I argue that this conflict overlapped with her acceptance of a female gender identity. The sustained nature of this conflict prevented her from establishing a metric of what I will call 'psychosomatic normality', with disastrous consequences when she began to suffer the symptoms of acute endometriosis. The memoir also shows the power of early life in determining how diseases are experienced subjectively, over time.